Chapter Una lettura dell'approccio quainiano alla cartografia attraverso la lente degli ingegneri geografi napoleonici - De Santi, Valentina (Territori, 2021)
Massimo Quaini wrote about ninety titles strictly connected to cartography in his long academic career and his large scientific production. Considering this quantity of works, the articles published by Quaini about geographic engineers' activity represent a seamless thread. In this contribution I examine such articles focusing on the heuristic motivations that have pushed him to put these actors at the centre of his historical-cartographic reflection.